2017
DOI: 10.1111/tpj.13642
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of lipids and metabolites during the cell cycle of Chlamydomonas reinhardtii

Abstract: Metabolites and lipids are the final products of enzymatic processes, distinguishing the different cellular functions and activities of single cells or whole tissues. Understanding these cellular functions within a well-established model system requires a systemic collection of molecular and physiological information. In the current report, the green alga Chlamydomonas reinhardtii was selected to establish a comprehensive workflow for the detailed multi-omics analysis of a synchronously growing cell culture sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
63
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(68 citation statements)
references
References 50 publications
2
63
0
3
Order By: Relevance
“…Lipids of Chlamydomonas are observed to show specific alterations in relation to the phase in the cell cycle; and three unique patterns can be seen (Juppner et al ., ). TAGs have shown a bimodal accumulation, with degradation occurring in the middle of the day, as well as at the beginning of the night.…”
Section: Lipid Degradation In Relation To Other Cellular Processesmentioning
confidence: 97%
“…Lipids of Chlamydomonas are observed to show specific alterations in relation to the phase in the cell cycle; and three unique patterns can be seen (Juppner et al ., ). TAGs have shown a bimodal accumulation, with degradation occurring in the middle of the day, as well as at the beginning of the night.…”
Section: Lipid Degradation In Relation To Other Cellular Processesmentioning
confidence: 97%
“…In the present study, we therefore conducted a systemic study to better understand the physiological and molecular response of Chlamydomonas to pharmacological‐induced TOR inhibition. Contrary to all the previous studies, we analyze the influence of rapamycin treatment on cell cycle dynamics, primary‐ and lipid metabolism, using synchronized cultures, grown under photoautotrophic conditions (Juppner et al ., ). In addition to using self‐sustaining growth conditions, we also included short‐term kinetic sampling throughout the complete diel cell cycle, allowing us to determine the timing and chronology of physiological and molecular changes after TOR repression.…”
Section: Introductionmentioning
confidence: 97%
“…Starch would be consumed for the cell division process in the dark and also in light, when energy could be provided directly by photosynthesis (Wanka, ; Vítová et al ., ). In a recent study of cell cycle of C. reinhardtii primary metabolites and lipids were followed throughout the diurnal cell cycle (Jüppner et al ., ). The authors showed that protein, DNA, and starch synthesis took place during light whereas cell division occurred during dark.…”
Section: Discussionmentioning
confidence: 97%
“…The approach used by Jüppner et al . () to study the cell cycle of the alga, including the synchronized growth of the photoautotrophic cell culture and the detailed metabolic phenotyping, can be combined with complex metabolic modelling as presented here, to understand the production and consumption of commercially useful metabolites. The experimental data needed to define the fate of storage molecules in the dark are the uptake rate of starch (or TAG) and the rate of protein synthesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation